Tindak Pidana Terhadap Kesusilaan Yang Dilakukan Tokoh Masyarakat Dari Sudut Pandang Kriminologi - Hartanto Hartanto (Jurnal Justiciabelen, 2020)
Crime continues to develop along with the development of society in all fields: political, economic, social, cultural and technological. Almost every day in the newspaper news, as well as electronic media, there is news about criminal acts against decency committed by various groups. Why it happened and how to overcome it is something that will be examined by the author. Cases of sexual decency against women, generally occur because of the imbalance of power relations in question is between men and women, and can also occur because of the imbalance of someone's "figure" in the community against the victim. Crime in general and in decency seems to develop along with the times, no longer see social status or figure. The role of culture, religion, and finally the law must always be fostered to be an element of handling crime against decency